The role of the Buddhist factor in political and civilizational processes in Mongolia - Zheleznyakov, Alexander S.; Nikiforov, Svyatoslav V. (The New Research of Tuva, 2025)
The article presents a retrospective analysis of the role of Buddhism in political and civilizational processes in Mongolia, based on the theoretical and methodological framework of civilizational political science. The authors examine the relationship between Buddhism and Mongolian identity, as well as the impact of Buddhist values on the country's history and culture.The study focuses on the period when Outer Mongolia gained sovereignty in the early 20th century, as well as on popular uprisings in Inner Mongolia at the turn of the 19th and 20th centuries. It also considers the controversial policies of the Mongolian People's Republic (MNR) towards Buddhism during the secular period. Finally, the article explores the features of Buddhism in post-secular Mongolia following the democratic revolution of 1990.Special attention is paid to the regional and interregional manifestations of the Buddhist factor in political and civilizational processes. These manifestations occur at the level of international relations within the Northeast Asian region, particularly within the Russia — China — Mongolia triangle. Additionally, they can be seen on a global scale through the internationalization of Buddhism by two major powers and the “third neighbor” of Mongolia.Issues such as the visits of the Dalai Lama to Mongolia, the legitimacy of Bogdo-gegan, and the historical role of Buddhism in international socialist projects like the Asian Buddhist Peace Conference are also discussed.
Keywords: civilizational political science; post-secularism; Mongolian civilization; Mongolia; Buddhism; Buddhist factor; civilizational space